1972
DOI: 10.1113/jphysiol.1972.sp009949
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin bleaching signals in essential night blindness

Abstract: SUMMARY1. The dark-adaptation curves of two subjects with essential night blindness revealed no evidence for functioning rod vision. Cone vision was normal.2. The photopupillomotor dark adaptation, and flash intensity response amplitude curves on one of these subjects confirmed the absence of rod function.3. However, there is the normal amount of rhodopsin in their rods with normal kinetics.4. Cone pigment kinetics are also nearly normal. After a full bleach, log threshold elevation of the foveal cones is line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…The first type is seen in CSNB patient 1 and shows normal rhodopsin concentrations in concord with data of Carr and Alpern (Carr, Ripps, Siegel and Weale, 1966;Alpern, Holland and Ohba, 1972). The second type, seen in CSNB patients 2 and 3, exhibits a pattern with negligible rhodopsin concentrations.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The first type is seen in CSNB patient 1 and shows normal rhodopsin concentrations in concord with data of Carr and Alpern (Carr, Ripps, Siegel and Weale, 1966;Alpern, Holland and Ohba, 1972). The second type, seen in CSNB patients 2 and 3, exhibits a pattern with negligible rhodopsin concentrations.…”
Section: Discussionsupporting
confidence: 66%
“…The Arden ratio of the electro-oculogram may be normal or decreased (Krill, 1977). Rod densitometry in four CSNB patients revealed no abnormalities (Carr et al, 1966a and1966b;Alpern, Holland and Ohba, 1972). Preliminary results of a densitometric study on seven CSNB patients by Keunen, van Meel and van Norren (1986) showed normal as well as decreased rod densities.…”
Section: Introductionmentioning
confidence: 99%
“…Although rod sensitivity is markedly reduced, the defect in CSNB cannot be attributed to a lack of rhodopsin. Measurements of rhodopsin density and the kinetics of bleaching and regeneration in patients with various forms of CSNB closely approximate those obtained from age‐matched normal subjects (Carr et al, 1966; Alpern et al, 1972; Ripps, 1982; Peachey et al, 1990; Sieving et al, 1995). However, when expressed in COS cells, the A292E, G90D, and T94I mutations were found capable of activating transducin constitutively in darkness and in the absence of 11‐ cis retinal, the rhodopsin chromophore (Dryja et al, 1993; Rao et al, 1994; Gross et al, 2003).…”
supporting
confidence: 62%
“…1. For human rods the concept of the equivalent background of the bleach (Crawford, 1947;Blakemore and Rushton, 1965) unifies results from a variety of different sizes of test, and this is compelling evidence for the idea of threshold elevation determined by an excitation pool of a large number of rods (Rushton, 1965 b;Alpern et al, 1972). But intracellular records from axolotl rods (Grabowski et al 1972) and extracellular recording from the skate retina treated with Na aspartate (Dowling and Ripps, 1972) provide just as convincing evidence that the threshold of each receptor itself is elevated by bleaching and backgrounds.…”
Section: Discussionmentioning
confidence: 98%